PERSEPSI IBU TERHADAP BERBAGAI MODEL GENDONGAN PERAWATAN METODE KANGURU (PMK): PILOT STUDY - sholihatul amaliya (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2019)
Background: The implementation of the Kangaroo Care Method (KMC) in Indonesia has been well developed. This is evidenced by the inclusion of KMC as one of the standard procedures in the care of low birth weight babies in many hospitals in Indonesia. The only one tool needed in implementing PMK is KMC clothes. PMK clothing models are widely used in Indonesia, namely the pouch (bag), Thari wrap and traditional wrap models. Objective: This study aims to identify mothers' perceptions of three different types of KMC carrier models Method: The study used crossover design involving 20 mothers with low birth weight (LBW) infants as responders, selected through a consecutive sampling method. Data were collected using a maternal perception questionnaire, maternal anxiety questionnaire, and KMC observation sheet. Result: The results of a repeated analysis of variance (ANOVA) showed that there was no significant difference in maternal perception when performing KMC with any of three KMC carriers (maternal perception p = 0.504, ? = 0.05). Conclusion: The type of KMC carrier model did not affect the perception of the mother so that the implementation of kangaroo mother care can use all three types of carriers models including kangaroo bag, thari wrap, and traditional wrap